STAFFING ISSUE IN CINEMA AND THEATER FIELD - Ochilova K. I. (American Journals Publishing, 2024)
This article talks about the issue of personnel in the field of cinema and theater in the Republic of Uzbekistan during the years of independence. Based on scientific data, the author studied and analyzed specific aspects of personnel issues in the field of cinema and theater based on available literature.
Keywords: Cinema, theater, art, culture, personnel.